Digital wellbeing tools through users lens - Mohamed Basel Almourad (17150983) (2021)
There is a growing recognition of excessive, compulsive, and hasty use of technology as an emerging form of problematic behavior affecting individuals' emotional, social, and occupational wellbeing. Smartphone overuse, in particular, has been linked to negative effects on users' quality of life, such as anxiety, depression, sleep disturbance and loss in productivity. One strategy to help regulate digital usage and, potentially, increase digital wellbeing is to devise smartphone applications to collect data about usage and increase users' awareness of it and enable them to set limits and alert users accordingly. However, such applications have not been extensively evaluated from the users' perspective and whether they help the basic requirements for digital wellbeing. In this paper, we examine the quality of the emerging family of digital wellbeing smartphone applications from the users' perspective and based on persuasive design and established behavioral change theories. We performed a thematic analysis on the users’ reviews on two popular applications, SPACE Break Phone Addiction and Google Digital Wellbeing (GDW). We report on the factors influencing user acceptance and rejection towards digital wellbeing applications and identify possible challenges and opportunities to improve their design and role in future releases. Other Information Published in: Technology in Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techsoc.2021.101778